Outcome of babies with no detectable heart rate before 10 minutes of age, and the effect of gestation. Issue 3 (25th October 2016) - Sproat, Thomas; Hearn, Richard; Harigopal, Sundeep
Abstract : Objective: Current resuscitation guidelines suggest that it is reasonable to consider stopping resuscitation where no heart rate (cardiac activity) has been detected for 10 min in a newborn baby from birth. We aimed to determine the mortality rate and 2-year neurodevelopmental outcome of all babies born with no heart rate before 10 min of age where resuscitation was attempted in a tertiary referral centre over a 5-year period. Design: To identify all babies with no heart rate before age 10 min we examined two groups: ▸ All babies classified as live born who received cardiac massage at birth between January 2009 and December 2013. ▸ All babies classified as stillborn between January 2009 and December 2013 where attempts were made at resuscitation beyond 10 min. Results: 87 babies received cardiac massage. 81 babies were live born and 6 were classified as stillborn. Twenty-two babies had no heart rate before 10 min of age. Eight babies survived to 2-year follow-up. 6/11 term babies survived, 2/4 babies born between 32 weeks and 37 weeks survived, and no infants born less than 32 weeks survived (n=7). Of the survivors, 5/8 had a normal neurodevelopmental outcome at 2 years' age. One patient was lost to follow-up, while the other two patients had hemiplegia. Conclusions: Our results add to the body of evidence suggesting that having no heart rate before 10 min of age, in term babies, may not be an appropriate prompt to discontinue resuscitation.